On Ordered G - Semigroups Containing Two-sided Bases - Jaroenram, Suchat; Jantanan, Wichayaporn; Nuadthaisong, Kodchakorn (Burapha Science Journal, 2026)
The aim of this paper is to study the concept of ordered G-semigroups containing two-sided bases that are studied analogously to the concept of G-semigroups containing two-sided bases considered by T. Changpas and P. Kummoon in 2018. Moreover, we prove any ordered G-semigroups containing two-sided bases have the same cadinality.